Sensory Mapping of UHT Milk with Single-Origin Chocolate - Dase Hunaefi; Sures Setiadi Tarigan; Elisabeth Dwinawati; Zen Fauzan Sholehuddin; Fahim Muchammad Taqi; Yves Henri Marie Zeller (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2023)
Like coffee, the popularity of speciality chocolate flavour or single-origin chocolate is growing in the Indonesian market. At the same time, sensory characteristic of the chocolate flavors is becoming more important, affecting both the taste and marketing of food product with chocolate flavor. As such, this study aims to describe UHT milk with single-origin chocolate through a complete sensory attribute mapping. A focus group discussion (FGD) resulted 15 texture attributes, 11 need-state attributes, 15 music attributes, 17 emotion attributes, 11 flavor attributes, and additional 70 color attributes. The complete sensory mapping test was performed using the CATA method based on attributes obtained from the FGD and analyzed using XLSTAT. The resulting product descriptions are as follows: cocoa Flores products were associated with soft and light textures, a need to focus and provide energy, pleasant classical and pop music, relaxed and warm emotions, flavors of ice cream, and light green, purple and brown colors. Cocoa Bali was linked to a smooth but rather hard texture, a need for rest and exercise, a cheerful musical style, happy emotions, a biscuit flavor, and a pink-yellow color. Cocoa Aceh was correlated with smooth and soft textures, state-of-the-art rest, energetic music, relaxed and energetic emotions, creamy flavor, and blue color. Meanwhile, cocoa Java was attributed with a smooth but rather hard texture, a state-of-the-art mood booster, cheerful music, relaxed emotions, ice cream flavor, and red-brown color. Thus, understanding specific sensory characteristics enables the producer to improve the product's development and marketing.